The Assets Agenda - Prabhakar, Rajiv. author. aut Link
XI, 167 p.
Keywords: Asset-based policies are becoming an increasingly important form of social policy globally. In this book, the first of its kind, Rajiv Prabhakar provides a theoretical perspective on the emerging asset agenda as well as examining specific policies, including the British Child Trust Fund.